Developing a software for BRAC bank unit/zonal office management system for smooth SME operation - Azad, Abul Kalam (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.